Social goals under a neoliberal agenda: measures to promote equality in European higher education read through a Foucauldian lens - Baciu, Elena-Loreni; Lazăr, Theofild-Andrei; Totan, Raluca Iunia (Frontiers in Sociology, 2025)
In this study we draw on Foucault’s work on governmentality and examine the power dynamics involved in establishing and implementing policies that promote equality in European higher education. Using a qualitative case study design, we selected 17 public universities situated in 13 European countries, from which we collected information about (1) the way these institutions problematize inequality in reference to participation in higher education, by labeling and categorizing vulnerable students and (2) the modes of governing and power tools (designed as support measures) they employ to address inequality. The results of the study show that the most typical profiles of vulnerability with which the universities in the sample engage include: students with disabilities, students from low-income backgrounds and students with children. Additionally, most universities use targeted support measures (as opposed to mainstreaming strategies) which consist in a mix of financial aid and support and adaptation services. The critical analysis of these measures reveals their power to shape students’ identifies and actions, through processes of subjectification, categorization, normalization and responsabilization. In the last section, we discuss the tension that appears between the European universities’ social dimension and the neoliberal policies that shape their functioning.